2008
DOI: 10.1002/ejic.200800091
|View full text |Cite
|
Sign up to set email alerts
|

DFT and Experimental Studies of Perchlorate Ion Coordination incis/trans‐Copper(II) Complexes of Tetradentate Pyridyl Ligands

Abstract: Spectral and structural studies of N, , where both NCH 3 groups are oriented in the same plane, is in equilibrium with its trans isomer and, as a result, a small energy difference (0.9 kcal mol -1 ) appears. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…The redox behaviors of [Cu(LMe2)] 2+ have also been reported. 2,3 The crystal structures of chromium(III) 4 and manganese(II) 5 with LMe2 and [Cu(ClO4)2(LMe2)] 6 have been reported. A couple of perchlorate ions in the [Cu(ClO4)2(LMe2)] coordinate to the [Cu(LMe2)] 2+ .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The redox behaviors of [Cu(LMe2)] 2+ have also been reported. 2,3 The crystal structures of chromium(III) 4 and manganese(II) 5 with LMe2 and [Cu(ClO4)2(LMe2)] 6 have been reported. A couple of perchlorate ions in the [Cu(ClO4)2(LMe2)] coordinate to the [Cu(LMe2)] 2+ .…”
mentioning
confidence: 99%
“…The crystal structure of copper(II) with its analogous N,N¢-dimethyl-N,N¢-bis(pyridine-2-ylmethyl)ethane-1,2-diamine (L¢Me2) and perchlorate ions has been also reported. 6 Only one perchlorate ion in [Cu(ClO4)(L¢Me2)]ClO4 coordinates to the Cu 2+ ion. Each N-methyl group of the [Cu(ClO4)(L¢Me2)]ClO4 is placed at a cis configuration.…”
mentioning
confidence: 99%
“…2 Å). The mean Cu II –O (triflate) bond length computed from 128 hits in the CSD was approximately 2.55 Å, which confirmed that triflate ions were weakly bonded in C3 …”
Section: Resultsmentioning
confidence: 66%
“…However, each the N-methyl groups for the perchlorate ioncoordinating [Cu(ClO4)2(LMe2)] was trans-configuration. 1 Therefore, the configuration did not only depend on the coordinating strength of anions, such as the weak coordinated pechlorate and the strong coordinated isothiocyanate ion. It is considered that it would depend on a concerted distortion of those Cu(II) complexes associated with a steric hindrance of the two N-alkyl groups in LRR' of a peripheral ligand with the coordinating strength of the coordinated anions.…”
Section: The Crystal Structures Of Nn¢-dimethyl-nn¢-bis(pyridin-2-ymentioning
confidence: 97%
“…perchlorate ([Cu(ClO4)2(LMe2)]) 1 and isothiocyanato-N,N¢-dimethyl-N,N¢-bis(pyridin-2-ylmethyl)propane-1,3-diaminecopper(II) perchlorate ([Cu(NCS)(LMe2)]ClO4) 2 have been reported. Each of the N-methyl groups is placed at a trans-and a cisconfiguration for [Cu(ClO4)2(LMe2)] and [Cu(NCS)(LMe2)]ClO4, respectively.…”
Section: The Crystal Structures Of Nn¢-dimethyl-nn¢-bis(pyridin-2-ymentioning
confidence: 99%